2016
DOI: 10.1371/journal.pone.0167578
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Derived Collagen for the Development of an Artificial Corneal Endothelial Graft. In Vivo Results in a Rabbit Model

Abstract: Corneal keratoplasty (penetrating or lamellar) using cadaveric human tissue, is nowadays the main treatment for corneal endotelial dysfunctions. However, there is a worldwide shortage of donor corneas available for transplantation and about 53% of the world’s population have no access to corneal transplantation. Generating a complete cornea by tissue engineering is still a tough goal, but an endothelial lamellar graft might be an easier task. In this study, we developed a tissue engineered corneal endothelium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 44 publications
3
19
0
1
Order By: Relevance
“…Several groups, including our own, 56 have already developed different artificial endothelial grafts that allow the recovery of endothelial functionality in different in vivo models. 18,27,29,57,58 From our point of view, SF films present several advantages, such as having better mechanical properties than other biomaterials, being a biomaterial that has been used for centuries in medicine and that could be easily accessible and have a lower cost of production than other biomaterials in some countries.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups, including our own, 56 have already developed different artificial endothelial grafts that allow the recovery of endothelial functionality in different in vivo models. 18,27,29,57,58 From our point of view, SF films present several advantages, such as having better mechanical properties than other biomaterials, being a biomaterial that has been used for centuries in medicine and that could be easily accessible and have a lower cost of production than other biomaterials in some countries.…”
Section: Discussionmentioning
confidence: 99%
“…Various properties of silicones make them favorable for biomedical uses, especially for wound dressings, including low liquid surface tension, high permeability, pressure sensitivity, mechanical resistance, and ease of sterilization . Moreover, there are several documented cases of using silicone to enhance the mechanical properties of more fragile biomaterials, especially in the case of wound dressings . As an example, Pires and Moares demonstrated the enhanced tensile strength and flexibility of chitosan–alginate membranes following incorporation of the liquid silicone rubber Silpuran 2130 A/B .…”
Section: Resultsmentioning
confidence: 99%
“…In regards of area and perimeter drop upon confluence, further studies required to determine if a stabilization or compaction process occurs as observed with human CECs [4,28,29] Total Protein, Pro-collagen I And Na/K-ATPase Concentration Total protein, pro-collagen I, and NA/K-ATPase concentrations were higher in CECs. A heterogeneous amount of CECs per group were evaluated due to their challenging isolation and culture.…”
Section: Cell Yieldmentioning
confidence: 99%
“…The clarity and nutrition of the cornea rely on these functions, given that it is an avascular tissue [3]. The damage to the corneal endothelium can lead to blindness because CECs are arrested in the G 1 cell cycle phase [4][5][6]. Corneal blindness can only be treated through transplantation, however, this procedure faces the shortage of tissue donors [3,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%